Effectiveness of Continuous Glucose Monitoring in a Clinical Care Environment: Evidence from the Juvenile Diabetes Research Foundation Continuous Glucose Monitoring (JDRF-CGM) trial (Diabetes care, 2010)
To determine whether continuous glucose monitoring (CGM) is effective in the management of type 1 diabetes when implemented in a manner that more closely approximates clinical practice. After completion of a 6-month randomized controlled trial (RCT) evaluating CGM in children, adolescents, and adults with type 1 diabetes, CGM was initiated in the trial's control group with less intensive training and follow-up than was included in the RCT. Subjects had an outpatient training session, two follow-up phone calls, and outpatient visits at 1, 4, 13, and 26 weeks. For subjects with baseline A1C > or =7.0%, the primary outcome was change in A1C at 6 months. CGM use decreased from a median of 7.0 days/week in the first month in the > or =25-year-old group, 6.3 days/week in the 15-24 year olds, and 6.8 days/week in the 8-14 year olds to 6.5, 3.3, and 3.7 days/week in the 6th month, respectively (P < 0.001 for each age-group). Among subjects with baseline A1C > or =7.0%, CGM use was associated with A1C reduction after 6 months (P = 0.02 adjusted for age-group). Severe hypoglycemia decreased from 27.7 events per 100 person-years in the 6-month control phase of the RCT to 15.0 events per 100 person-years in the 6-month follow-up CGM phase (P = 0.08). Frequent use of CGM in a clinical care setting may improve A1C and reduce episodes of hypoglycemia. However, sustained frequent use of CGM is less likely in children and adolescents than in adults.